SiC detectors: A review on the use of silicon carbide as radiation detection material - De Napoli, Marzio (Frontiers in Physics, 2022)
Silicon Carbide (SiC) is a wide bandgap semiconductor with many excellent properties, which make it one of the most promising and investigated materials for radiation particle detection. This review surveys the key advantages and the current experimental state of the field. The main aspects related to material properties, growth techniques, doping, defects, electrical contacts and characterization methods are summarized, with an highlight on how these can be related to detector performance. The most recent and significant experimental results on the use of SiC diodes to detect electrons, protons, alpha, ions, UV radiation, x-gamma rays, thermal and fast neutrons, are discussed. Finally, the effects of high temperature operation and radiation damage on detector performance are outlined.